2013
DOI: 10.1080/07391102.2013.790141
|View full text |Cite
|
Sign up to set email alerts
|

210 Computational study of substrates and mediators features of lacasses

Abstract: Laccases are enzymes of the family of the multicopper oxidases, being widely used for biotechnological applications. The enzyme catalytic cycle consists in the oxidation of the substrate with the concomitant reduction of molecular oxygen to water. In the process the substrate is converted to a free radical, that can oxidize larger substrates acting as a mediator or it can undergo polymerization. Substrate binding is not specific and there is a large diversity of substrates for laccases. Moreover, the binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Figure 6 shows the exploration results when using both ABTS protonation states: the doubly negatively charged or the neutral (protonation at the mid nitrogen) species. Clearly, while the neutral species introduces a well-defined minima (dark blue color in Figure 6 ), the negative substrate does not show any apparent binding pocket in the surface (cyan color in Figure 6 ); the dominance of the neutral species seems to agree with the optimal pH and with previous studies ( Delavari and Perez, 2013 ). Importantly, the binding minima is located at ∼5Å from Ala316s beta carbon, presenting a significant penetration into the active site entrance pocket, Figure 7 .…”
Section: Resultssupporting
confidence: 83%
“…Figure 6 shows the exploration results when using both ABTS protonation states: the doubly negatively charged or the neutral (protonation at the mid nitrogen) species. Clearly, while the neutral species introduces a well-defined minima (dark blue color in Figure 6 ), the negative substrate does not show any apparent binding pocket in the surface (cyan color in Figure 6 ); the dominance of the neutral species seems to agree with the optimal pH and with previous studies ( Delavari and Perez, 2013 ). Importantly, the binding minima is located at ∼5Å from Ala316s beta carbon, presenting a significant penetration into the active site entrance pocket, Figure 7 .…”
Section: Resultssupporting
confidence: 83%
“…It was observed that the results of computer simulations used to study laccase agreed well with corresponding experimental data, indicating a high degree of reliability. Delavari et al (2013) performed docking to characterize the laccase binding pocket of different species in order to establish their common pharmacophoric characteristics. A common km value was also rationalised for a specific substrate oxidised by different laccases.…”
Section: Resultsmentioning
confidence: 99%